Physical fitness test performance in firefighter trainees: Differences between graduated and released trainees and predicting academy graduation. - Lockie, Robert G.; Orr, Robin M.; Montes, Fernando; Dawes, J. Jay (Work, 2024)
BACKGROUND: Fitness tests have been previously used to predict academy graduation and highlight specific capacities to be targeted in applicants/trainees to optimise their potential for academy success. OBJECTIVE: To compare the fitness of graduated and released (did not complete academy requirements) firefighter trainees and explore using decision tree analysis to predict academy graduation via fitness tests. METHODS: Retrospective analysis was conducted on 686 trainees who completed an occupational physical ability test (OPAT): Illinois agility test; push-ups; pull-ups; leg tucks; estimated maximal aerobic capacity (VO2max); backwards overhead 4.54-kg medicine ball throw; 10-repetition maximum deadlift; and 91.44-m farmer's carry. Data were recorded in raw and scaled scores (tests scored from 0–100; maximum OPAT score was 800). Trainees were split into 'graduated' (GRAD; n = 576) or 'released' (REL; n = 110) groups. Mann-Whitney U-tests compared between-group OPAT scores. A decision tree analysis using Chi-square automatic interaction detection was conducted, with raw and scaled scores entered into the analysis. A separate analysis was conducted with only the raw scores. RESULTS: GRAD trainees outperformed REL trainees in all OPAT events (p < 0.001). OPAT total score was the best predictor of academy graduation (p < 0.001), followed by the deadlift score (p = 0.003). Estimated VO2max was the only significant raw score predictor (p < 0.001). CONCLUSIONS: GRAD trainees were fitter than the REL trainees. Fitness could predict trainees who graduated from the academy. Overall fitness (OPAT total score), muscular strength (deadlift) and aerobic capacity were important graduation predictors. Training staff could develop these fitness qualities in their trainees to potentially improve fire academy graduation rates.